The role and meaning of the word in the art of Uzbek dubbing - Sh.T. Yusupov (Genius Journals, 2022)
While the introduction of sound into cinema radically changed the character of cinema, the introduction of the "word" along with sound gave a dramatic twist to cinema. This process laid the foundation for the development of the art of dubbing. At present, dubbing has been technically formed and has risen to the level of art, the article discusses the history, development period and creators of dubbing art.
Keywords: Cornering; Dubbing; Biological Aspects; Proportional Articulation